Association between Gender and Plaque Index- A Retrospective analysis of 86,000 patient records over nine months - S, VAISHALI.; BALASUBRAMANIAM, ARTHI; DURAISAMY, REVATHI (The journal of contemporary issues in business and government, 2021)
Dental plaque is the community of microorganisms found on a tooth surface as a biofilm, embedded in a matrix of polymers of host and bacterial origin. If not removed regularly, the biofilm undergoes maturation and the resulting pathogenic bacterial complex can lead to dental caries, gingivitis and periodontitis. Dental plaque is seen in both genders and it depends on each individual’s oral hygiene maintenance, which prevents progression of disease such as gingivitis and periodontitis. The aim of the study is to evaluate the association of gender with the amount of plaque. Retrospective study was conducted using patient records of University hospital. Consecutive case sheets with plaque index records were retrieved. Data was entered in excel and coded, then imported to SPSS. Descriptive statistics and Peasron’s chi square association tests were done. The results were represented in the form of stacked bars. In this study, it was observed that out of 1152 patients, 51% were males and 49% were females. In relation to distribution of plaque index interpretation, out of 1152 patients, 41.44% had good plaque index scores, 33.45% had fair plaque index scores and 25.11% had poor plaque index scores.Plaque index was good for males (22.59%) than females (18.85%). There was no statistically significant association found between gender and amount of plaque (Chi square test=5.266,p= 0.621). Amount of plaque accumulation is more in females with no association between gender and plaque index.